2020
DOI: 10.3892/mmr.2020.10981
|View full text |Cite
|
Sign up to set email alerts
|

SHARPIN regulates cell proliferation of cutaneous basal cell carcinoma via inactivation of the transcriptional factors GLI2 and c‑JUN

Abstract: SHanK-associated rH domain-interacting protein (SHarPin) is a component of the linear ubiquitin chain assembly complex that can enhance the nF-κB and JnK signaling pathways, acting as a tumor-associated protein in a variety of cancer types. The present study investigated the role of SHarPin in cutaneous basal cell carcinoma (Bcc). Human Bcc (n=26) and normal skin (n=5) tissues, and Bcc (Te354.T) and normal skin (HacaT) cell lines were used to evaluate SHarPin expression level using immunohistochemistry and wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…The c-Jun transcription factor was the first oncogenic transcription factor discovered, and is the cellular homologue of v-Jun [ 44 ]. Studies have found that c-Jun with physiological functions can promote embryonic liver development and liver and skin regeneration [ 45 ]. Moreover, c-Jun is implicated in carcinogenesis and development of many tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The c-Jun transcription factor was the first oncogenic transcription factor discovered, and is the cellular homologue of v-Jun [ 44 ]. Studies have found that c-Jun with physiological functions can promote embryonic liver development and liver and skin regeneration [ 45 ]. Moreover, c-Jun is implicated in carcinogenesis and development of many tumors.…”
Section: Discussionmentioning
confidence: 99%
“…There are three major types of skin cancers: basal cell carcinoma (BCC), squamous cell carcinoma (SCC), and melanoma. SHARPIN is downregulated or absent and highly mutated in cancer nests and precancerous BCC and SCC lesions compared with normal skin samples [ 134 , 135 ]. Knockdown of SHARPIN in TE354.T cells, a human BCC cell line, enhanced tumor cell proliferation, possibly due to the increased phosphorylation of two transcriptional factors, c‑JUN and GLI family zinc finger 2 (GLI2) [ 134 ].…”
Section: Introductionmentioning
confidence: 99%
“…SHARPIN is downregulated or absent and highly mutated in cancer nests and precancerous BCC and SCC lesions compared with normal skin samples [ 134 , 135 ]. Knockdown of SHARPIN in TE354.T cells, a human BCC cell line, enhanced tumor cell proliferation, possibly due to the increased phosphorylation of two transcriptional factors, c‑JUN and GLI family zinc finger 2 (GLI2) [ 134 ]. By contrast, higher expression of SHARPIN correlates with worse survival of melanoma [ 119 ].…”
Section: Introductionmentioning
confidence: 99%